Residual Networks - Architectural Innovations and Beyond: Studying Architectural Innovations and Applications of Residual Networks (ResNets) for Improving Training and Performance in Deep Learning Tasks (Advances in Deep Learning Techniques, 2024)
Residual Networks (ResNets) have revolutionized deep learning by addressing the vanishing gradient problem, enabling the training of very deep neural networks. This paper provides a comprehensive overview of architectural innovations in ResNets and their applications across various domains. We explore the original ResNet architecture, highlighting its key components such as skip connections and residual blocks. Additionally, we discuss advancements such as pre-activation, wide ResNets, and densely connected networks (DenseNets), which further improve the training and performance of ResNets. Furthermore, we examine the applications of ResNets in computer vision, natural language processing, and speech recognition, showcasing their effectiveness in various tasks. Finally, we discuss future research directions and challenges in the field of residual networks.
Keywords: Residual Networks; ResNets; Deep Learning; Architectural Innovations; Skip Connections; Training; Performance; Computer Vision; Natural Language Processing; Speech Recognition